Presidential Decree-Law No. 102/2012 Amending Some Provisions of the General Sales Tax Law No. 11 of the year 1991 - Egypt (2025)
Presidential Decree-Law No. 102 of the year 2012 amending some provisions of the general sales tax law no. 11 of the year 1991 قرار رئيس جمهورية مصر العربية بالقانون رقم 102 لسنة 2012 بتعديل بعض أحكام قانون الضريبة العامة على المبيعات الصادر بالقانون رقم 11 لسنة 1991